Patterns of contact call differentiation in the panmictic East African Abyssinian White‐eye Zosterops abyssinicus (Aves: Passeriformes). Issue 24 (9th December 2015) - Habel, Jan Christian; Husemann, Martin; Ulrich, Werner
Abstract: Species distribution patterns range from highly disjunct to continuous, depending on their ecological demands and the availability of respective habitats. East African savannahs are mostly interconnected and ecologically comparatively homogenous and thus provide a prerequisite for a rather panmictic distribution pattern for species occurring in this habitat. The Abyssinian white‐eye Zosterops abyssinicus is a savannah inhabiting bird species, representing such a continuous distribution. This species occurs in high abundances and is very mobile, and past population genetic studies have suggested that gene flow is high and genetic differentiation is low even across relatively large geographic distances. Further, only little morphological differences were found. In order to test for potential divergence in acoustic traits despite its interconnected geographic distribution, we analyzed 2795 contact calls of Z. abyssinicus, which were recorded at 19 sites across Kenya. Our data indicate weak, but significant differentiation in call characteristics across latitudinal gradients. We found strong changes in call characteristics in populations where Z. abyssinicus occurs in sympatry with its highland congener, Zosterops poliogaster . However, the changes in call characteristics in sympatry were in different directions and lead to strong differentiation of the sympatric populations to other conspecific populations potentially representing a case of cascade reinforcement. The detected spatial gradients likely result from ecological differences and balancing effects of natural and sexual selection. Abstract : Abyssinian White‐eyes, Zosterops abyssinicus, here at Mt. Kulal, are common in the lowlands of East Africa, but can also be found at higher elevations. The species has an interconnected distribution across major parts of East Africa; despite its panmictic distribution the birds show significant divergence in contact calls with latitudinal and longitudinal gradients.